2013
DOI: 10.1175/jcli-d-12-00253.1
|View full text |Cite
|
Sign up to set email alerts
|

ENSO Contribution to Aerosol Variations over the Maritime Continent and the Western North Pacific during 2000–10

Abstract: This study investigates interannual aerosol variations over the Maritime Continent and the western North Pacific Ocean and aerosol-cloud-precipitation relationship during the period 2000-10 based on monthlymean anomalies. The local aerosol-cloud-precipitation relationship displays strong regional characteristics. The aerosol variation is negatively correlated with cloud and precipitation variation over the Maritime Continent, but is positively correlated with cloud and precipitation variation over the region s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 57 publications
1
21
0
1
Order By: Relevance
“…4a) was greater than that of DJF (Fig. 4b), which is consistent with Wu et al (2013). The standard deviation of interannual variation in AOD in SON was 0.072, whereas that in DJF was 0.018.…”
Section: Seasonal Difference Of Interannual Variation In Aod Over Thesupporting
confidence: 85%
See 1 more Smart Citation
“…4a) was greater than that of DJF (Fig. 4b), which is consistent with Wu et al (2013). The standard deviation of interannual variation in AOD in SON was 0.072, whereas that in DJF was 0.018.…”
Section: Seasonal Difference Of Interannual Variation In Aod Over Thesupporting
confidence: 85%
“…Recently, some previous studies suggested that interannual precipitation variation controls AOD on interannual time-scale by using these stored observational data (e.g., Jeoung et al 2014;Wu et al 2013). However, there are few studies also focusing on the aerosol-cloud-precipitation interactions although aerosol also affects cloud properties, such as CER and cloud number concentration, and precipitation development.…”
Section: Introductionmentioning
confidence: 99%
“…), which indicates that ENSO may affect the haze pollution over East Asia through influencing the monsoon circulation. Wu et al (2013) found that the aerosol variations over the Maritime Continent and western North Pacific presented a biennial feature, which could be attributed to the impacts of ENSO. From the results of Wu et al (2013), it seemed that ENSO only influenced the aerosols over eastern China (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) • N, 110-120 • E) around October in El Niño or La Niña developing years and July in El Niño or La Niña decaying years.…”
Section: Introductionmentioning
confidence: 94%
“…Wu et al (2013) found that the aerosol variations over the Maritime Continent and western North Pacific presented a biennial feature, which could be attributed to the impacts of ENSO. From the results of Wu et al (2013), it seemed that ENSO only influenced the aerosols over eastern China (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) • N, 110-120 • E) around October in El Niño or La Niña developing years and July in El Niño or La Niña decaying years. Gao and Li (2015) revealed statistically and through case analyses that El Niño (La Niña) events were more likely to bring about more (fewer) haze days in eastern China (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) • N, 105-122.5 • E).…”
Section: Introductionmentioning
confidence: 94%
“…Precipitation predictability can lead to aerosol predictability, once a precipitationÁaerosol relationship is established. Studies addressing ENSO impacts on aerosols exist; for instance, Wu et al (2013) revealed a biennial component of aerosol variability over the Maritime Continent (58SÁ58N, 95Á1358E) and the western North Pacific Ocean. The novelty of the current study is to analyse the fine-mode aerosol optical depth (fAOD) in relation to ENSO.…”
Section: Introductionmentioning
confidence: 99%